Sosialisasi Produk-Produk Bank Syariah Sebagai Solusi Riba - Utama, Fikri Rizki (Jurnal Nusantara Mengabdi, 2023)
Purpose: Indonesia is an agricultural country, so the profession as a farmer is a profession that many people choose. So the service wants to increase the knowledge of Gapoktan Farmers in Gantiwarno village regarding sharia banking products to avoid usury transactions. Methodology: This service was carried out in Gantiwarno Village, Pekalongan District, East Lampung Regency at the Gapoktan Farmer Group. The method of service carried out is by conducting socialization and conducting discussions and questions and answers with socialization participants. Results: Achieved an increase in knowledge of Gapoktan Farmers in Gantiwarno Village, East Lampung who took part in socialization events regarding sharia banking and BSI products. Then there is a need to increase the effectiveness of more specific Islamic economic education in every line of society. And there is a need to socialize sharia banking through resource development strategies. Limitation and contribution: Some obstacles in the field are: (1) Several Gapoktan Farmers felt that the BSI technology features were still not well understood and used by them. Because most Gapoktan members do not have smartphones, (2) There is still a lack of basic religious knowledge in the Gantiwarno Village community. So the Service Team provided several suggestions such as: (1) It would be better for Gapoktan Farmers to have personal smartphones, (2) Understanding related to religious knowledge in general also needs to be increased, such as the existence of scientific Islamic studies in the mosques in Gantiwarno village.